Surface-induced phenomena in uncompensated collinear antiferromagnets. (5th February 2015) - Charilaou, M; Hellman, F
Abstract: The net spontaneous magnetization of antiferromagnets with modified surfaces was computed using mean-field theory. For ordinary phase transitions the net magnetization of uncompensated AFM is smaller than the surface magnetization and the Néel vector, whereas for extraordinary phase transitions the net magnetization is larger than the surface magnetization and the Néel vector at finite temperature. Moreover, the temperature dependence of these three observable internal parameters changes drastically with the surface properties, i.e. the surface exchange coupling J S . Based on these findings, contour plots showing different regions of magnetization and Néel vector behavior as functions of temperature and surface exchange strength are proposed.